Management of postpartum pulmonary embolism combined with retained placenta accreta: A case report. Issue 38 (September 2019) - Tong, An; Zhao, Fumin; Liu, Ping; Zhao, Xia; Qi, Xiaorong
Abstract: Rationale: Retained placenta accreta is an increasing obstetric problem in recent years, and pulmonary embolism (PE) during pregnancy and the postpartum period is a vital condition, but lack of standard therapy guidelines. This report describes a case of postpartum PE combined with retained placenta accreta. Patient concerns: A 27-year-old woman presenting with fever and dyspnea after delivery was admitted to our hospital with retained placenta accreta. Diagnoses: The patient was diagnosed with the infection, postpartum PE, and residual placenta. Interventions: The antibiotics and low molecular weight heparin were initially started to cure the infection and control PE. Mifepristone was then used to promote the necrosis of residual placenta while long-term use of warfarin was served as continuous anticoagulant therapy. Hysteroscopic resection of retained placenta was not performed until thrombi had been almost disappeared after more than 2 months of anticoagulation therapy. Outcomes: The patient's menstruation returned to normal within several weeks after hysteroscopic resection and she completely recovered from PE after 3 months of anticoagulant therapy. Lessons: Treatment of retained placenta accreta can be postponed when encountering complicated cases, such as postpartum PE. PE in perinatal stage can be managed referring to nonmaternal PE.